The effect of moisture content on the grinding performance of corn and corncobs by hammermilling - Probst, Kyle V.; Ambrose, R. P. Kingsly; Pinto, R. L.; Bali, R.; Krishnakumar, P.; Ileleji, K. E. (My University, 2013)
The grinding behavior of corn and corncobs was investigated at moisture content levels of 10.39%, 16.02%, and 19.64% (wet basis) for shelled corn and 10.04%, 14.65%, and 20.13% (wet basis) for corncobs. Grinding performance was assessed by determining the throughput, specific rate of breakage, particle size distribution, power consumption, and energy required for grinding using a hammermill. The physical and flow properties investigated were loose and tapped bulk density, compressibility index, Hausner ratio, particle density, and static angle of repose. The throughput and specific rate of breakage of corncobs were very low compared to corn and decreased with increasing moisture content. The energy required for grinding corncobs was higher than that for corn. The particle size of ground corn was smaller than that of ground cobs; however, there were no significant differences across moisture levels. The particle size distribution of ground corn was narrower than that of ground cobs. Physical and flow properties were not significantly different across moisture levels for both ground corn and cobs. The smaller size of the corn particles explains why the bulk density, compressibility index, Hausner ratio, and angle of repose were higher for ground corn than for ground cobs.
Keywords: Corn; Corncobs; Grinding behavior; Particle size distribution; Physical properties